Mammalian Mitophagosome Formation: A Focus on the Early Signals and Steps - Zachari, Maria; Ktistakis, Nicholas T. (Frontiers in Cell and Developmental Biology, 2020)
Mitophagy, a conserved intracellular process by which mitochondria are eliminated via the autophagic machinery, is a quality control mechanism which facilitates maintenance of a functional mitochondrial network and cell homeostasis, making it a key process in development and longevity. Mitophagy has been linked to multiple human disorders, especially neurodegenerative diseases where the long-lived neurons are relying on clearance of old/damaged mitochondria to survive. During the past decade, the availability of novel tools to study mitophagy both in vitro and in vivo has significantly advanced our understanding of the molecular mechanisms governing this fundamental process in normal physiology and in various disease models. We here give an overview of the known mitophagy pathways and how they are induced, with a particular emphasis on the early events governing mitophagosome formation.